The Relationship between Internal Locus of Control and Academic Self-Regulation in Class 11 Vocational High School Students in Sidoarjo: Hubungan Antara Internal Locus of Control Dengan Regulasi Diri Akademik pada Siswa Kelas 11 Sekolah Menengah Kejuruan di Sidoarjo - Syahputra, Indra Agi; Affandi, Ghozali Rusyid (Universitas Muhammadiyah Sidoarjo, 2021)
This research is motivated by the phenomenon of students regarding the problem of managing academic self-regulation in learning activities at school. This study aims to determine the relationship between Internal Locus of Control and Academic Self Regulation in class XI students of SMK